An experimental study of responses to armed police in Great Britain - Yesberg, Julia A. (Journal of experimental criminology, 2021)
Objectives This study tested whether the presence of a firearm changed the way people reacted to police among a British sample. Method In an online study, participants were shown images of armed and unarmed police and rated them on a number of variables. Some participants were primed to think about terrorism, and some participants were exposed to more armed police than others. Results Participants had more negative responses to police when they were armed. We found no effect of the terrorism prime on people’s reactions to images of armed police and no effect of exposure. Yet, unexpectedly, we found a negative effect of the terrorism prime on trust and legitimacy. Conclusions In a country where police have never before been routinely armed, this research raises important questions about how armed police can retain the public’s support when they may no longer be considered ‘prototypical representatives’ of the British people.